Honokiol Mitigates Metabolic-Associated Fatty Liver Disease by Regulating Nrf2 and RIPK3 Signaling Pathways - Cao, Wen; Chen, Zengdian; Lin, Chenhui; Lin, Xiaojin; Chen, Yang; Zhang, Jingjuan (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Metabolic-associated fatty liver disease (MAFLD) is a common cause of chronic liver disease worldwide. However, there is currently no recognized effective drugs for treating it. Materials and Methods: In this study, we investigated the efficacy of Honokiol (HNK) in vitro for mitigating MAFLD. Then, 0.4 mM palmitic acid (PA) and LO2 cells were used to establish the MAFLD model. The protective effect of HNK on MAFLD was confirmed by Oil Red O staining and cell counting kit (CCK-8) assay in LO2 cell line. Quantitative real-time polymerase chain reaction (qRT-PCR) and Western blot were carried out to analyze the regulatory role of HNK on Nrf2 and RIPK3 signaling pathways. The effect of HNK and its downstream signaling pathways on oxidative stress were verified by the detection of reactive oxygen species (ROS), malondialdehyde (MDA), catalase (CAT), and superoxide dismutase (SOD). The concentration of IL-1β, IL-6L, and TNF-α was assessed by enzyme-linked immunosorbent assay (ELISA). Results: The middle concentration of HNK (50 μmol/L) was selected as the best option for inhibiting lipidosis and oxidative stress in MAFLD models. Honokiol mitigates MAFLD via activation of nuclear factor E2-related factor 2 (Nrf2) signaling pathways in vitro. Honokiol suppressed MAFLD via activating the Nrf2 signaling pathway to play an antioxidant and anti-inflammatory role. Also, HNK regulates Nrf2 and RIPK3 signaling pathways to mitigate MAFLD. Conclusion: Our results showed that HNK may suppress the oxidative stress and inflammation in MAFLD via activation of Nrf2 signaling pathway. Cite this article as: Cao W, Chen Z, Lin C, Lin X, Chen Y, Zhang J. Honokiol mitigates metabolic-associated fatty liver disease by regulating Nrf2 and RIPK3 signaling pathways. Turk J Gastroenterol. 2024;35(7):551-559.